Research and characterization of Cryptosporidium spp. in the domestic cat (Felis catus): First description of C. felis in the state of Goiás and C. muris in the Midwest region of Brazil - Barrios, Leda Margarita Castaño; de Paula, Lorrayne Honorio; Bosso, Fernando Borges; Soares, Vando Edésio; Meireles, Marcelo Vasconcelos [UNESP]; Moraes, Dunya Mara Cardoso; Linhares, Guido Fontgalland Coelho; dos Reis, Jenner Karlisson Pimenta; Teixeira, Weslen Fabricio Pires; de Sá Jayme, Valéria (Elsevier, 2025)
With the increasingly close coexistence between pets and humans, coupled with reports of Cryptosporidium cross-infection between felines and their guardians, research aimed at understanding the epidemiology of these parasites in specific regions has become necessary. The principal objective of this study was to undertake a molecular characterization of Cryptosporidium in fecal samples from felines in the state of Goiás, Brazil (which is unprecedented for the region), and to assess the risk factors involved in the infection of these animals in the aforementioned locale. A total of 95 fecal samples were collected from domestic felines in the municipality of Goiânia, Goiás, Brazil. All the animals involved were categorized by sex (male or female), lifestyle (stray or domiciled), and age (under six months or six months and older). After collection, all fecal aliquots underwent genomic DNA extraction, followed by a nested PCR (nPCR) technique targeting the 18 s rRNA gene. Subsequently, sequencing of all amplified products was performed to diagnose Cryptosporidium parasites. In addition to searching for Cryptosporidium in feces, all felines underwent serological testing for Feline Immunodeficiency Virus (FIV) antibodies (IgG) using the Enzyme-Linked Immunosorbent Assay (ELISA). Of all the fecal samples analyzed, 17.9 % (17/95) tested positive for the presence of Cryptosporidium spp. DNA, with the variable “age under six months” being the only statistically significant risk factor (p ≤ 0.05) for feline infection. C. felis was the most prevalent species, identified in 88.2 % (15/17) of the positive samples. C. muris was the second most diagnosed species, confirmed in 5.9 % (1/17) of the positive samples. Of all the feline serological samples evaluated, 48.42 % (46/95) were positive for anti-FIV IgG. It was confirmed that 75 % (3/4) of all adult animals positive for Cryptosporidium showed positive (50.00 % [2/4]) or indeterminate (25.00 % [1/4]) results for FIV. This unprecedented study provides the first report of parasites from the genus Cryptosporidium in domestic felines in the state of Goiás, including the first report of C. felis in the state and of C. muris in Midwest Brazil.
Keywords: C. felis; C. muris; Cats; Cryptosporidiosis; Risk factors; Zoonosis